Performing Resistance: Imagining Nation in Sama’s Play Amar Singha - Shobhakant Regmi, (Interdisciplinary Journal of Management and Social Sciences, 2022)
Framing the concept of performance as a mode of resistance in aesthetic production is itself a rigorous act, nevertheless this article aims to unleash how these modes of resistance are articulated through the characters in the historical play, Amarsingh (1991) by Balakrishna Sama. The performance of the characters, as such; Amar, Girvana, Balabhadra, Ranajor Singh and the soldiers involved in the Anglo- Nepal war on border disputes during the19th century shed the light on Nationalist mode of resistance against their enemies (firangees). Mostly, the spontaneous counteracts as they pose from side to side against the frontier enemies are akin to imagine a ‘consolidated nationalism’ as a whole. In this context, Sama’s play Amarsingh lays the foundation to imagine nation as a whole through the mode of ‘writing back’ as performing the resistance.